2017
DOI: 10.3390/molecules22111851
|View full text |Cite
|
Sign up to set email alerts
|

Marrubium vulgare L. Leave Extract: Phytochemical Composition, Antioxidant and Wound Healing Properties

Abstract: Several factors contribute in wound generation, e.g., accidental traumas or surgery, and in certain cases, this dermal injury may have a devastating outcome. When skin damage occurs, the human body puts in place a sophisticated choreography, which involves numerous repairing processes to restore physiological conditions. Nevertheless, natural healing mechanisms are ineffective towards chronic or non-healing wounds and thus, therapeutic strategies may represent the only beneficial alternative to counteract thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 50 publications
3
64
1
3
Order By: Relevance
“…Previous reported in vitro antioxidant activity studies, it was observed that M. vulgare aerial parts showed different and varying results. It can be concluded that this may due to the differences of the locations and extraction methods of the plant material [18][19][20][21]. In addition the plant material of the previous studies were either grown in cell culture or collected from various sites without standardization concerns, which is one of the major differences of our plant material, resulting difficult comparisons in this aspect.…”
Section: Antioxidant Activitiesmentioning
confidence: 99%
“…Previous reported in vitro antioxidant activity studies, it was observed that M. vulgare aerial parts showed different and varying results. It can be concluded that this may due to the differences of the locations and extraction methods of the plant material [18][19][20][21]. In addition the plant material of the previous studies were either grown in cell culture or collected from various sites without standardization concerns, which is one of the major differences of our plant material, resulting difficult comparisons in this aspect.…”
Section: Antioxidant Activitiesmentioning
confidence: 99%
“…Throughout the world, a huge percentage of population depends upon the use of plantbased medicine because of their easy availability and also due to the lack of better healthcare alternatives. Plant-based medicines or herbal medicines have been effective and safe traditional methods practiced in many countries including China, India, and most African countries for the treatment of various diseases [2]. A large number of plant extracts, concoctions, poultices, decoctions, or pastes are equally used in many countries for treatment of diseases, cuts, wounds, and burns.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of plant extracts, concoctions, poultices, decoctions, or pastes are equally used in many countries for treatment of diseases, cuts, wounds, and burns. Thus, since antiquity, several medicinal plants and plant-based strategies are widely known for their significant role in wound healing and skin regeneration as well as their therapeutic applications [2].…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature has evidenced that Marrubium vulgare shows several in vivo and in vitro activities including antihypertensive, antioxidant, antiinflammatory, antidiabetic, effects on respiratory system, digestive stimulant, antiasthmatic, hypolipidemic, antibacterial, and antifungal effects. Within this context, and as a part of our current research in this field, in the present contribution we focused on M. vulgare L. (white/common horehound), an annual herbaceous plant belonging to Lamiaceae family, native to Eurasia and northern Africa zones . Due to its biological activities, the European Medicines Agency has published a monograph for M. vulgare in which all the traditional, non‐clinical and clinical data are reported .…”
Section: Introductionmentioning
confidence: 99%